Some aspects of the biology of Todarodes sagittatus (Cephalopoda: Ommastrephidae) from the Balearic Sea (Western Mediterranean) - Quetglas, Antoni; Alemany, Francesc; Carbonell, Aina; Merella, Paolo; Sánchez, Pilar (Scientia Marina, 1998)
A total of 346 individuals (152 males and 194 females) of Todarodes sagittatus caught by commercial trawlers working down to 800 m in the Balearic Sea (Western Mediterranean) was studied. Data are presented on size frequency distributions, length-weight relationships, and relationships between mantle length and various measurements of the beak. Some aspects of the reproductive biology (maturity and gonad development) were also determined. Reproductive period could be situated in the second half of the year, since the number of mature individuals was maximum from July to October for males and from September to December for females. The sex ratio was found to be significantly different from 1:1 only outside this second semester. No individual appeared in hauls performed below 100 m depth and the greatest frequency of appearance was between depths of 400 and 800 m. All mature females were caught deeper than 500 m, indicating that spawning could take place from this depth. The mean mantle length increased with depth, suggesting a possible ontogenic migration.